Analysis of Change Management, Value Co-Creation Strategies and Student Satisfaction on Customer Relationship Management in Selected Malaysian Higher Education Institutions - Lee, Lian Fey (2024)
In response to the intense competition and fragmented implementation of customer relationship management (CRM) in Malaysian private higher education institutions, this quantitative exploratory study investigates the impact of change management and value co-creation strategies on the effectiveness of CRM within this sector, with a particular emphasis on student satisfaction as a mediating factor. The study examines five change management strategies: Selling Change, Change Infrastructure, Training, Organizational Structure, and Incentives, as well as two value co-creation strategies: Student Participation and Participatory Communication. The study sampled 507 management staff members from 32 institutions affiliated with the Malaysian Association of Private Colleges and Universities (MAPCU), which includes both private universities and branch campuses of foreign universities. These institutions represent a substantial portion of the top-ranked Malaysian private universities in the QS World University Rankings 2023. Data were collected using a purposive sampling method and analysed with SmartPLS software. The analysis confirmed the reliability and validity of the constructs, as evidenced by strong Cronbach's Alpha values, composite reliability exceeding the acceptable threshold, and robust Average Variance Extracted (AVE) values. Furthermore, the square root of the AVE supported the discriminant validity of the constructs. Findings revealed that participatory communication significantly affects the effectiveness of customer relationship management (CRM). In contrast, training exhibited an unexpected negative association, suggesting a misalignment with CRM objectives. Change infrastructure and organizational structure demonstrated marginal significance, while selling change, incentives, and student participation showed no significant direct effects on CRM. However, the mediated effects of student satisfaction revealed significant relationships with Customer Relationship Management (CRM) for most strategies. The strategies of Selling Change, Change Infrastructure, and Organizational Structure positively influenced CRM through student satisfaction. The negative or insignificant impacts of Training and Incentives indicate a need for strategic realignment. Notably, Participatory Communication had a significant direct impact on both CRM effectiveness and student satisfaction, underscoring its importance in CRM outcomes. While the direct impact of Student Participation on CRM effectiveness was less pronounced, it significantly enhanced student satisfaction. These findings underscore the mediating role of student satisfaction across all strategies, highlighting its significance in improving Customer Relationship Management (CRM) outcomes in Malaysian private higher education institutions. The study offers valuable insights for administrators to refine CRM strategies, enhance the student experience at every touchpoint of the learning journey, and address challenges related to student enrolment and retention. This approach ensures a more cohesive and integrated implementation of CRM. Additionally, it emphasizes the necessity of incorporating change management, value co-creation, and student satisfaction to bolster CRM effectiveness. Future research could further investigate these findings in various educational contexts and assess their long-term impacts on institutional performance.